Transcriptome and methylome analysis reveals three cellular origins of pituitary tumors - Taniguchi-Ponciano, Keiko (Sci Rep, 2020)
Pituitary adenomas (PA) are the second most common intracranial tumors. These neoplasms are classified according to the hormone they produce. The majority of PA occur sporadically, and their molecular pathogenesis is incompletely understood. The present transcriptomic and methylomic analysis of PA revealed that they segregate into three molecular clusters according to the transcription factor driving their terminal differentiation. First cluster, driven by NR5A1, consists of clinically non-functioning PA (CNFPA), comprising gonadotrophinomas and null cell; the second cluster consists of clinically evident ACTH adenomas and silent corticotroph adenomas, driven by TBX19; and the third, POU1F1-driven TSH-, PRL- and GH-adenomas, segregated together. Genes such as CACNA2D4, EPHA4 and SLIT1, were upregulated in each of these three clusters, respectively. Pathway enrichment analysis revealed specific alterations of these clusters: calcium signaling pathway in CNFPA; renin-angiotensin system for ACTH-adenomas and fatty acid metabolism for the TSH-, PRL-, GH-cluster. Non-tumoral pituitary scRNAseq data confirmed that this clustering also occurs in normal cytodifferentiation. Deconvolution analysis identify potential mononuclear cell infiltrate in PA consists of dendritic, NK and mast cells. Our results are consistent with a divergent origin of PA, which segregate into three clusters that depend on the specific transcription factors driving late pituitary cytodifferentiation.